Race and Anti-Racist Online Coping as Moderators of College Adjustment Associated with Exposure to Social Media Racism among Asian, Black, and Hispanic/Latine Students. - Park, Yea Won; Tao, Xiangyu; Fisher, Celia B. (Journal of Youth & Adolescence, 2025)
With the rise of social media, racism in the digital landscape has become ubiquitous potentially impacting the academic adjustment of college students of color. The role of anti-racist online coping strategies, such as seeking resources, support, and actively managing social networks in mitigating the negative effects of online racism has been understudied. Racial group differences and anti-racist online coping were examined as moderators between online discrimination and college adjustment among Asian, Black and Hispanic/Latine college students. The sample consisted of 772 emerging adults of color (M = 20.37, SD = 1.56, 44.8% women; 32.4% Asian, 35% Black, 32.6% Hispanic/Latine). Overall, average and high coping levels moderated the association between discrimination and college adjustment, but the protective effect varied by race and domain of adjustment. Across educational, relational and psychological dimensions of adjustment, protective effects of anti-racist online coping were stronger among Asian students, partially effective for Black students, and least effective for Hispanic/Latine students, and psychological adjustment was most vulnerable. These findings underscore the importance of understanding how students of color experience and take part in the digital landscape and providing institutional supports that help students effectively utilize anti-racist online strategies to mitigate the adverse effects of social media racism on their adjustment to college.